Gendering modernism a historical reappraisal of the canon - Bucur-Deckard, Maria 1968- (London Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"A critical narrative of how gender norms and the modernist movement shaped one another in the early 20th century, using vivid case studies"--Provided by publisher.
"Gendering Modernism offers a critical reappraisal of the modernist movement, asking how gender norms of the time shaped the rebellion of the self-avowed modernists and examining the impact of radical gender reformers on modernism. Focusing primarily on the connections between North American and European modernists, Maria Bucur explains why it is imperative that we consider the gender angles of modernism as a way to understand the legacies of the movement. She provides an overview of the scholarship on modernism and an analysis of how definitions of modernism have evolved with that scholarship. Interweaving vivid case studies from before the Great War to the interwar period--looking at individual modernists from Ibsen to Picasso, Hannah Höch to Josephine Baker--she covers various fields such as art, literature, theatre and film, whilst also demonstrating how modernism manifested itself in the major social-political and cultural shifts of the 20th century, including suffragist feminism, psychology, sexology, eugenics, nudism, anarchism, communism and fascism. This is a fresh and wide-ranging investigation of modernism which expands our definition of the movement, integrating gender analysis and thereby opening up new lines of enquiry. Written in a lively and accessible style, Gendering Modernism is a crucial intervention into the literature which should be read by all students and scholars of the modernist movement as well 20th-century history and gender studies more broadly"--Provided by publisher.
Prologue -- Introduction: What Sort of Rebellion? -- 1. Modernism before the Great War -- 2. Modernism Flourishes -- 3. The Modernist Canon : How Did it Come About? -- 4. A New Set of Criteria : Rebellion, Rejection, and Reimagining Modernism.
Includes bibliographical references and index.
Keywords: Women and the arts -- United States -- History#y20th century; Women and the arts -- Europe -- History -- 20th century; Arts, Modern -- 20th century; Arts, Modern -- Philosophy; Sex role -- History -- 20th century; Social movements -- History -- 20th century; Arts and society -- History -- 20th century; United States -- Intellectual life -- 20th century; Europe -- Intellectual life -- 20th century